Plant pathology - Sharma, P. D. (Alpha Science International Ltd., 2006)
The book examines the host-pathogen interactions in the light of new tools and techniques of molecular biology and genetics. Scope of integrating microbial biopesticides in the management of pathogens, pests and weeds of agriculture and forestry has been evaluated. An account of over 150 important crop plant diseases of international importance including those of recent etiology are presented